Ornament in Architecture: Symbol Representation - Aysu Akalın; İrem Durgut (DEPARCH Journal of Design Planning and Aesthetics Research)
This study aims to provide a new framework for the position of ornament by examining the link between ornament and “the body” as well as its interaction with decorative arts. In this sense, Ernst Cassirer’s concepts of symbol and representation which follow Immanuel Kant transcendental philosophy and Kant’s dichotomy of free and adherent beauty, are investigated. Within the scope of the article, theorists who discuss ornament with artistic expression are divided into two groups; in the first, Ruskin treats ornament and the body relationship as a “symbol”, while others, such as Louis Sullivan and Gottfried Semper, use the combination of both as if it is a “symbol”. As Sullivan and Semper reveal, a symbol reflecting the highest artistic creation also requires a process of reinterpretation and abstraction of the figural ornamentation. As emphasized, the position of ornament in the relationship of architecture to other arts has always been complex and has been unable to be identified with a definite framework since the Renaissance. Leon Battista Alberti, an Italian humanist, architect, and the primary developer of Renaissance art theory, achieves the perfect whole, expressing the highest artistic creation, via the reinterpretation and abstraction of figured forms. However, Alberti’s humanist approach differs from John Ruskin’s holistic view to the relationship between figural arts and architecture. Although, Alberti and Ruskin disagree in theory, it is shown that Alberti’s harmonious geometric whole, somehow corresponds to Kant’s purposefulness based on his transcendental scheme. It is concluded that the theoretical conceptualization of figural ornamentation with a metaphorical understanding of the human body expresses Cassirer’s symbol / perfect whole, which can only be obtained by achieving perfect mathematical unity between part and whole.